Orexin Receptor Competitive Antagonists: A Novel target of the Sedative and hypnotics drugs for the pharmacotherapy of Insomnia - Banerjee, Indrajit (Nepal Journal of Epidemiology, 2018)
Orexins are peptide neurotransmitters which are produced in the lateral and posterior part of the hypothalamus in the brain. There are two Orexin receptors which has been identified till date viz. Orexin 1 (OX 1) and Orexin 2 (OX 2 receptor).